Rethinking peace mediation : challenges of contemporary peacemaking practice / edited by Catherine Turner and Martin Wählisch. - Turner, Catherine (Law teacher); Wählisch, Martin, 1982- (Bristol University Press, 2021)
Written by international practitioners and scholars, this pioneering work offers insights into the peace mediation practice and explains how multifaceted assistance has become an indispensable part of it. With its policy focus and real-world examples, this is a go-to resource for researchers and advisers involved in peace processes.